The distally-based island ulnar artery perforator flap for wrist defects - Karki Durga; Singh A (Indian Journal of Plastic Surgery)
Background: Reconstruction of soft tissue defects around the wrist with exposed tendons, joints, nerves and bone represents a challenge to plastic surgeons, and such defects necessitate flap coverage to preserve hand functions and to protect its vital structures. We evaluated the use of a distally-based island ulnar artery perforator flap in patients with volar soft tissue defects around the wrist. Materials and Methods: Between June 2004 and June 2006, seven patients of soft tissue defects on the volar aspect of the wrist underwent distally-based island ulnar artery perforator flap. Out of seven patients, five were male and two patients were female. This flap was used in the reconstruction of the post road traffic accident defects in four patients and post electric burn defects in three patients. Flap was raised on one or two perforators and was rotated to 180°. Results: All flaps survived completely. Donor sites were closed primarily without donor site morbidity. Conclusion: The distally-based island Ulnar artery perforator flap is convenient, reliable, easy to manage and is a single-stage technique for reconstructing soft tissue defects of the volar aspect of the wrist. Early use of this flap allows preservation of vital structures, decreases morbidity and allows for early rehabilitation.